Granulocytic sarcoma of the pancreas on 18F-FDG PET/CT: A case report. Issue 49 (December 2016) - Ishii, Akira; Kondo, Tadakazu; Oka, Tomomi; Nakamoto, Yuji; Takaori-Kondo, Akifumi
Abstract: Rationale: Granulocytic sarcoma (GS) is defined as leukemia infiltration in any organ other than the bone marrow. GS rarely occurs in the pancreas. Here, we present the first report of GS in the pancreas on 18 F-fluorodexyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT). Patient concerns: A 19-year-old male patient with acute myeloid leukemia received a human leukocyte antigen-haploidentical stem cell transplant as a second transplant while in second complete remission. Interventions: After a second stem cell transplant, obstructive pancreatitis accompanied by a mass in the pancreatic head was observed. FDG-PET/CT revealed abnormal activity in the head of the pancreas and the skin in the patient's left breast area. Diagnoses: Pathological examination demonstrated relapsed acute myeloid leukemia in both the lesions. Outcomes: This is the first report showing the 18 F-FDG PET/CT findings of GS in the pancreas. Lessons: 18 F-FDG PET/CT may help determine the stage of GS.